Production of peptide-specific antibody against protein P10 of Southern rice black-striked dwarf virus - Hanh, Do Thi; Thu Hang, Pham; Thanh Ha, Nguyen; Thu Ha, Nguyen Thi; Thi Thu Huong, Phung; Xuan Hoi, Pham; Duy Phuong, Nguyen (Vietnam Journal of Biotechnology, 2021)
Virus Southern rice black-striked dwarf virus (SRBSDV) disease caused serious damage rice growing areas in Northern and Central Vietnam over the past decade. While the application of SRBSDV diagnostic methods based on the Reverse transcription polymerase chain reaction (RT-PCR) technique was impossible due to technical complexity, simpler SRBSDV diagnostic techniques using specific antibody have not yet been developed in Vietnam. The biggest difficulty right now was the absence of commercial specific antibodies against SRBSDV. To develop diagnostic techniques by enzyme-linked immunosorbent assay (ELISA) for SRBSDV detection, in a previous study, we created antibodies against SRBSDV from the 66 kDa recombinant SRBSDV protein P10 expressed in E. coli; the obtained antibodies had a titer of 1:5000 dilution. Here, we continued to produce polyclonal antibodies against SRBSDV from small antigenic peptide (PASTTDVTHYGGY) derived from the P10 envelope protein, which was consevative in Vietnamese SRBSDV population. Titer of the purified IgG antibody was exmined using Dot enzyme-linked immunosorbent assay (Dot-ELISA) which showed a titer of 1:40000 dilution. The specific binding between anti-peptide IgG antibodies diluted at 1:40000 and the recombinant P10 protein in E. coli extraction was confirmed by using western blotting. In Dot-ELISA, our antibodies could distinguish between the SRBSDV-infected and non-infected rice samples. Our research results open up a new opportunity for developing the rapid diagnosis Southern rice black-striked dwarf virus membrane-type kit in Vietnam.